2012
DOI: 10.1111/j.1399-3038.2012.01349.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific oral tolerance induction with raw hen’s egg in children with very severe egg allergy: A randomized controlled trial

Abstract: Six months of SOTI with raw HE emulsion resulted in partial tolerance, with regular intake, in a significant percentage of children with severe egg allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 30 publications
3
61
2
Order By: Relevance
“…Despite the fact that control patients were younger and therefore they had more likely to develop natural tolerance. Our results are similar to those obtained by other researchers reporting 70%‐90% success with total desensitization, equivalent to one whole raw egg or one raw egg white …”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that control patients were younger and therefore they had more likely to develop natural tolerance. Our results are similar to those obtained by other researchers reporting 70%‐90% success with total desensitization, equivalent to one whole raw egg or one raw egg white …”
Section: Discussionsupporting
confidence: 92%
“…Several prior studies have shown some success in using these approaches for single specific food allergens such as milk [8-15], egg [13,14,16-18], peanut [19-24], and hazelnut [25]. These current types of experimental treatments need to be tested for optimization in safety, efficacy, and length of time [26-34].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new trials using protocols that omit a rush escalation phase known as home-based OIT, have been used due to the improved safety associated with these methods. Our regimen also omits the rush escalation phase, and is unique in that we used an intermittent loading dose (i.e., 2 to 3 times a week) instead of daily loading as in previous home-based OITs [14,18-20]. In order to ensure safety, we also kept a fixed dose throughout the maintenance period at home, and avoided any escalations, as indicated in previous protocols [14,18-20].…”
Section: Discussionmentioning
confidence: 99%
“…Our regimen also omits the rush escalation phase, and is unique in that we used an intermittent loading dose (i.e., 2 to 3 times a week) instead of daily loading as in previous home-based OITs [14,18-20]. In order to ensure safety, we also kept a fixed dose throughout the maintenance period at home, and avoided any escalations, as indicated in previous protocols [14,18-20]. The advantage of intermittent loading is the safety demonstrated by the number of adverse events related to doses administered at home; 45/10380 (0.43%) for home-based OIT throughout the current study period, which is considerably better than that of the previous studies ranging from 0.99% to 24.2% [14,18,20,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation